Short Form of Mental Health Literacy Questionnaire for Adults: Psychometric Properties of Serbian Version - Marina Kovacevic Lepojevic PhD; Ana Radanovic MA; Marija Trajkovic MA; Luka Mijatovic PhD; Isidora Micic MA (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Mental health literacy (MHL) has been widely explored by researchers who focus on youth mental health. However, there is little data related to the validity and reliability of the tools for the assessment of MHL constructs. The present study aimed to adapt the short version of Mental Health Literacy Questionnaire for young adults in Serbian sample and examine its psychometric properties. Translation and adaptation of items were performed using the following procedures: item are translated from English or Serbian by a bilingual translator and using a think-aloud procedure, back-translation, semantic comparison of the translation, and analysis of the translated version by the original version of the manuscript. The sample consisted of 369 participants aged 17 to 47 years, which is in accordance with the recommended number of participants needed for quantitative instrument validation studies. Confirmatory factor, internal consistency, and external validity analyses were performed. The results supported the validity of a shorter version of the questionnaire (MHLq-SVa), composed of 16 items that fit with four previously defined MHL dimensions (knowledge, beliefs, help-seeking intentions, and self-help strategies). Internal consistency, between-factor correlations, and correlations with other relevant mental health constructs further supported the adequacy of the instrument’s psychometric properties. We recommend the MHLq-SVa as valid and reliable measure for assessing MHL in young adults and encourage further exploration at more diverse and representative samples.